Improvement of currency legislation and liberalization of the currency market in Ukraine - Zeltser, R.; Stoliar М. (Ways to Improve Construction Efficiency, 2020)
The article highlights the main advantages of improving currency legislation and liberalizing the foreign exchange market in Ukraine. It is determined that in accordance with the Law of Ukraine "On Currency and Currency Transactions", a modern approach is being implemented, which is based on the principle: "less risks - less attention, more risks - more attention". An overview of the reliefs provided for under the new Law has been carried out: free opening of accounts of legal entities abroad, payments in foreign currency on foreign currency government bonds, currency swaps of banks with residents and non-residents, non-delivery forwards and forwards of debt and foreign currency operations currency and banking metals by legal entities, making payments in foreign currency during life insurance, accumulation of currency in the accounts of legal entities for repayment of foreign currency their borrowings, unlimited investments of banks in securities of investment class, investments and credits of residents from hryvnia LORO-accounts of non-resident banks, investments in Ukraine also in currencies of the 2nd group of the classifier of currencies, and also it is envisaged to improve business conditions and provision of services for the population . The basic principles of conducting currency transactions are considered, namely: the principle of freedom of currency transactions, the principle of risk orientation, transparency, sufficiency and effectiveness of currency regulation, the principle of independence and marketability of currency regulation. The structure of the Law, model of currency regulation, scheme of organization of currency regulation, principles of conducting currency transactions, factors and sequence of measures on liberalization of currency regulation are considered. A set of factors that significantly improve the effectiveness of the currency regulation and currency surveillance system is characterized. The issue of gradual removal of currency restrictions on current and financial operations, reduction of intervention of the central bank and authorities in the functioning of the currency market, bringing it in compliance with international norms are considered.